2020
DOI: 10.21037/gs-20-547
|View full text |Cite
|
Sign up to set email alerts
|

Biparametric (bp) and multiparametric (mp) magnetic resonance imaging (MRI) approach to prostate cancer disease: a narrative review of current debate on dynamic contrast enhancement

Abstract: Prostate cancer is the most common malignancy in male population. Over the last few years, magnetic resonance imaging (MRI) has proved to be a robust clinical tool for identification and staging of clinically significant prostate cancer. Though suggestions by the European Society of Urogenital Radiology to use complete multiparametric (mp) T2-weighted/diffusion weighted imaging (DWI)/dynamic contrast enhancement (DCE) acquisition for all prostate MRI examinations, the real advantage of functional DCE remains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 86 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…As recommended by the PIRADS committee, the current role of DCE is limited to type 3 lesions to determine the nature of equivocal lesions ( 7 ). Although the sensitivity of DCE is high, but its specificity may be low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As recommended by the PIRADS committee, the current role of DCE is limited to type 3 lesions to determine the nature of equivocal lesions ( 7 ). Although the sensitivity of DCE is high, but its specificity may be low.…”
Section: Discussionmentioning
confidence: 99%
“…Since the diagnostic performance of the bpMRI method is not inferior to that of the mpMRI, the application of the bpMRI method requires high image quality and reader expertise ( 7 ). In this study, we retrospectively analyzed the clinical data of 699 patients who underwent prostate biopsy from January 2018 to March 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, DCE has a secondary role in the PI-RADS evaluation of clinically significant PCa [43]. However, when used together with T 2 W and DWI images (depending on the lesion location), it can be useful for detecting small lesions and characterizing indeterminate findings [42,44].…”
Section: Standardization and Reproducibilitymentioning
confidence: 99%
“…In 2019, the PI-RADS version 2.1 was newly described, and a simplified biparametric MRI (bpMRI) comprising T2WI and DWI was proposed (5). To date, many studies have demonstrated that the use of bpMRI protocols don't significantly reduce PCa detection rates and is comparable to mpMRI protocols (6)(7)(8). Meanwhile, bpMR protocols also have several advantages, such as a shorter examination time, reducing cost and avoiding potential adverse effects of gadolinium-based contrast agents.…”
Section: Introductionmentioning
confidence: 99%